Dispute Settlement Practices through the Religious Court’s Mobile Court (Sidang Keliling) - Hazar Kusmayanti; Sherly Ayuna Puteri (Fiat Justisia: Jurnal Ilmu Hukum, 2020)
This research is attempted to analyze the practices of mobile court and compare it with others. Based on the results of the study, the conclusions that can be obtained are that the implementation of the circuit court conducted at the Tasikmalaya District Religious Court has fulfilled several principles of civil procedural law, namely fast, simple and low cost. Among them when people who experience obstacles to come to the court office for reasons of distance, transportation and costs of the court come directly to the location, the bureaucracy is not complicated meaning that the implementation of the trial must be completed no later than 4 times the hearing, and the existence of an effective control system and various elements. Obstacles in the conduct of circuit courts include no standard guidelines for the holding of circuit courts, not all cases registered by residents are resolved in circuit courts, limited budgets, cases that have not been heard are all without prodeo, facilities and infrastructure, and not all religious courts hold circuit courts.